Toward a divinised poetics: God, self, and poeisis in W. B. Yeats, David Jones, and T. S. Eliot - Soud, W (2013)
This thesis examines the traces of theological and broader religious discourses in selected works of three major twentieth-century poets. Each of the texts examined in this thesis encodes within its poetics a distinct, theologically derived conception of the ontological status of the self in relation to the Absolute. Yeats primarily envisions the relation as one of essential identity, Jones regards it as defined by alterity, and Eliot depicts it as dialectical and paradoxical. Critics have underestimated the impact on Yeats’s late work of his final and most sustained engagement with Indic traditions, which issued from his friendship and collaboration with Shri Purohit Swami. Though Yeats projected Theosophical notions on the Indic texts and traditions he studied with Purohit, he successfully incorporated principles of Classical Yoga and Tantra into his later poetry. Much of Yeats’s late poetics reflects his struggle to situate the individuated self ontologically in light of traditions that devalue that self in favor of an impersonal, cosmic subjectivity. David Jones’s The Anathemata encodes a religious position opposed to that of Yeats. For Jones, a devout Roman Catholic committed to the bodily, God is Wholly Other. The self is fallen and circumscribed, and must connect with the divine chiefly through the mediation of the sacraments. In The Anathemata, the poet functions as a kind of lay priest attempting sacramentally to recuperate sacred signs. Because, according to Jones’s exoteric theology, the self must love God through fellow creatures, The Anathemata is not only circular, forming a verbal templum around the Cross; it is also built of massive, rich elaborations of creaturely detail, including highly embroidered and historicized voices and discourses. Critics have long noted the influence of Christian mystical texts on Eliot’s Four Quartets, but some have also detected a countercurrent within the later three Quartets, one that resists the timeless even as the poem valorizes transcending time. This tension, central to Four Quartets, reflects Eliot’s engagement with the dialectical theology of Karl Barth. Eliot’s deployment of paradox and negation does not merely echo the apophatic theology of the mystical texts that figure in the poem; it also reflects the discursive strategies of Barth’s theology. The self in Four Quartets is dialectical and paradoxical: suspended between time and eternity, it can transcend its own finitude only by embracing it.